Culture and customs of Israel - Torstrick, Rebecca L., 1954- (Culture and customs of the Middle East., 2004)
Students and other readers looking to more fully understand and appreciate Israelis of all backgrounds and their ways of life and culture now have a solid source of engaging, balanced, and accurate information. Israel's brief, turbulent history and the Arab-Israeli conflict are always taken into account in the narrative; however, the emphasis here is nonpolitical and encompassing of the heterogenous culture of its citizens, including Jews, Arabs, Druze, and others. The predominant Jewish culture itself is multicultural, with immigrants from all over the world.